2018
DOI: 10.7189/jogh.08.010703
|View full text |Cite
|
Sign up to set email alerts
|

Starting the conversation: community perspectives on preterm birth and kangaroo mother care in southern Malawi

Abstract: BackgroundDespite introduction of Kangaroo Mother Care (KMC) in Malawi over a decade ago, preterm birth remains the leading cause of neonatal mortality. Although KMC is initiated in the health care facility, robust community follow-up is critical for survival and optimal development of preterm and low birth weight infants post-discharge. The objective of this qualitative study was to gain insight into community and health worker understanding, attitudes, beliefs and practices around preterm and low birth weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 30 publications
(22 reference statements)
4
46
0
Order By: Relevance
“…Messages/guidelines in the Malawi antenatal counselling standard operating procedures (SOPs) does not integrate KMC awareness at the ANC service delivery point [ 32 , 33 ], which is aiding inconsistency in KMC message acquisition amongst mothers at ANC clinics in various health facilities, although,. Lydon et al , observed that the ANC clinic was the important arena to disseminate KMC messages to the targeted population, who are at risk of LBWI delivery [ 34 ]. This study indicated increased number of pregnancies as one of the high risk factors of LBWIs deliveries in MD catchment area, which serves as the indicators to dissemination of KMC messages at ANC clinics and strengthening strategies of family planning methods uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Messages/guidelines in the Malawi antenatal counselling standard operating procedures (SOPs) does not integrate KMC awareness at the ANC service delivery point [ 32 , 33 ], which is aiding inconsistency in KMC message acquisition amongst mothers at ANC clinics in various health facilities, although,. Lydon et al , observed that the ANC clinic was the important arena to disseminate KMC messages to the targeted population, who are at risk of LBWI delivery [ 34 ]. This study indicated increased number of pregnancies as one of the high risk factors of LBWIs deliveries in MD catchment area, which serves as the indicators to dissemination of KMC messages at ANC clinics and strengthening strategies of family planning methods uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified other factors beyond the wrap influencing KMC practices, including inadequate staffing levels and capacity, limited provision of information about KMC to mothers during antenatal care/shortly after birth, inadequate equipment and supplies to support mothers' adherence to recommended KMC practices, dedicated space, addressing the pain and fatigue of mothers in facilities and support to the mothers post-discharge, and weak recording and reporting on KMC [5,[10][11][12]15]. These other challenges also warrant further examination to improve the quality of KMC implementation in Malawi.…”
Section: What We Recommend?mentioning
confidence: 99%
“…The study also found little engagement of husbands in the support of skin-to-skin, contact, regardless of the wrap used. The level of family and social support has been previously identified as an important enabler for KMC practices in Malawi [6,11,27]. Though there is not enough evidence on the involvement of fathers in increasing adherence to KMC [3], several studies report that stigma around male involvement in child care prevents KMC uptake [27,28].…”
Section: What We Recommend?mentioning
confidence: 99%
See 1 more Smart Citation
“…We did not query its acceptability in this present study, but other investigators have found it to be well received and generally acceptable, particularly after the benefits are explained. [74][75][76][77][78][79][80] Additional responses referenced the theme of help being available for the baby at these centers, including keeping the baby warm and giving oxygen. One respondent referenced corticosteroids for fetal maturity.…”
Section: Management Of Ptbmentioning
confidence: 99%